Regulations and community participation in education funding at the elementary education level - Muhammad Nur Huda; Soedjono Soedjono; Nurkolis Nurkolis; Rosalina Br. Ginting; Marevic Jean Lutog (Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of education funding regulations and community participation in the management of basic education funding in Pemalang Regency, Central Java. The study used a mixed-methods approach with a convergent parallel design, combining a quantitative survey of 203 basic education teachers and Focus Group Discussions (FGDs) with local education stakeholders. The data were analysed through descriptive statistics and thematic analysis, followed by data integration. The results indicate that local government regulations on education funding are in the very good category, while community participation and the condition of education funding are in the good category. The results emphasise the need for a legal umbrella in the form of a Regional Regulation on the implementation of education that regulates the responsibilities of local governments and strengthens community participation. This study concludes that the success of education funding depends on strong regulations and effective collaboration among the government, the community, and educational institutions.